George Clooney, by Paul McDonald - Gillian Kelly (Alphaville: Journal of Film and Screen Media, 2020)
In one of the latest additions to the BFI Film Stars series, Paul McDonald turns the spotlight on the filmic and extrafilmic career of contemporary male performer George Clooney (1961–). Edited by Martin Shingler and Susan Smith, the series launched in 2012 with the former’s general guide, Star Studies: A Critical Guide, and the latter’s individual star study Elizabeth Taylor. The editors state an overarching aim of producing one hundred titles over a twenty-year period, each profiling a separate performer from Western and world cinema.